2021
DOI: 10.1364/prj.411825
|View full text |Cite
|
Sign up to set email alerts
|

Smart ring resonator–based sensor for multicomponent chemical analysis via machine learning

Abstract: A. Q. (2021). Smart ring resonator-based sensor for multicomponent chemical analysis via machine learning. Photonics Research, 9(2),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The training set accounts for 70%, and the test set accounts for 30%. 8 , 9 , 19 , 23 The 70% of the data is randomly selected as the training set each time and the remaining 30% is retained as the validation set during clinical sample training process. The training process performs iterations of twenty large cycles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The training set accounts for 70%, and the test set accounts for 30%. 8 , 9 , 19 , 23 The 70% of the data is randomly selected as the training set each time and the remaining 30% is retained as the validation set during clinical sample training process. The training process performs iterations of twenty large cycles.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, a series of good studies about optofluidic imaging systems combined artificial intelligence (AI) for smart disease diagnosing are gradually emerging, 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 which implies a potential possibility of combining optical imaging and AI technologies for convenient and accurate smart blood coagulation function diagnoses. Blood clotting is a continuous process that includes clotting activation, formation, and densification, and the patients differ in the rate and intensity of each process.…”
Section: Introductionmentioning
confidence: 99%
“…The sensing of chemical compounds for monitoring or detection is necessary for various fields and industries 12 . 3 Integrated optical sensors offer a cost-effective and scalable solution, 4 as well as the opportunity to integrate with electronics to achieve an effective lab-on-a-chip that is compact and portable. 5 Integrated optical sensing falls into two categories, either detecting the real component n of the medium in refractive index sensing, or determining the imaginary component k through absorption sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the multilayer perceptron (MLP) creates the opportunity to solve these two problems. Recently, Li et al demonstrated an MLP regressor-enabled NIR ring sensor 76 for decomposing the resonant spectrum that records the resonant peak shift over time. Compared with the resonant spectrum, the absorption spectrum contains more distinctive information about the molecule and is the main characteristic leveraged in the MIR region.…”
mentioning
confidence: 99%